Design of Computer Based 12 Lead ECG Using STM32F401 Microcontroller - Reyhan Issatyadi Darmawan; Arf Surtono; Donni Kis Apriyanto; Amir Supriyanto (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The research of designing computer-based 12 lead ECG using STM32F401 microcontroller has been done. ECG is a healthcare device recording heart electrical activity and assesses heart condition. ECG was chosen for health condition check-ups because it is low-cost and can monitor heart conditions in real-time. To get more details about a heart condition, an ECG with more than one lead is required, of which 12 leads are used for diagnostic application. The designed ECG uses a computer to display and record the ECG signal from the human body using a GUI program created with Visual Studio 2019, capable of recording 12 leads simultaneously and using USB to connect to the computer. STM32F401 is used as a digital signal processor to filter the ECG signal to make a good quality and noise-free ECG recording. Specifying the designed 12 lead ECG is a signal gain of 384 times with error less than 5%, 115.05 dB CMRR, and 0.05-200 Hz frequency response suitable for diagnostic application. The ECG was also capable of recording ECG signals from the human body.